Motion Sensor Based Chemistry Fitness Game on Factors Affecting Reaction Rate - Khaerunnisa Khaerunnisa; Ferli Septi Irwansyah; Ida Farida (UIN Fatmawati Sukarno Bengkulu, 2026)
Digital technology-based chemistry learning today is still dominated by passive screen based activities, resulting in a sedentary learning pattern that negatively impacts student engagement and physical health. This study aims to develop a Motion Sensor-based Chemistry Fitness Game on the material factors affecting the rate of reaction and to test its feasibility through expert validation and limited trials. The study uses a Design Based Research (DBR) method with three stages, namely Define, Design, and Develop. The Chemistry Fitness Game integrates educational games, interactive rewards, and a virtual laboratory with collision theory visualization in a single QuestLab-based learning flow. The motion sensor (accelerometer) functions as the main interaction mechanism, where students shake their smartphones to increase the visualized values of temperature or concentration through changes in moving particles and collision frequency. The expert validation results obtained an average validity coefficient of r = 0.88 with a high category, while a limited trial on 15 Chemistry Education students obtained an average user response percentage of 93.8% with a very good category. These results indicate that Chemistry Fitness Game is feasible to be used as an interactive chemistry learning media that integrates physical activity into the learning process, so that learning is no longer limited to passive screen interaction.